Architecture now! - Jodidio, Philip, 1954- (Köln : Taschen, 2005)
TASCHEN's 25th anniversary - Special edition! The best of contemporary architectural design The crème de la crème of the most influential architects and architectural firms - the definitive reference guide to contemporary architectural design. Here you'll find familiar names, such as O. Gehry, Meier, Ando, Foster, and Starck, as well as a host of brilliant future stars. Highlights include Jakob & MacFarlane's morphological George Restaurant at the Centre Georges Pompidou, Paris, Diller & Scofidio's "Blur Building" proposal for the International Expo 2001 in Switzerland, and Herzog & De Meuron's remarkable Tate Modern. Arranged alphabetically by architect or firm, with biographical and contact information for designers and an extensive selection of photographs and illustrations, this volume presents the highlights of Architecture Now! Vol 1. The author: Philip Jodidio has written more than fifteen books on contemporary architecture, including monographs on Tadao Ando, Norman Foster, Richard Meier and Alvaro Siza. He has been the Editor-in-Chief of Connaissance des Arts, the most widely distributed French art monthly, since 1980.
Keywords: Architectuur -- Geschiedenis -- 20ste eeuw; Architectuur -- 1990-.